Global SWOT Strategies Revolutionize Sandal Craftsmen Revenue - Rizka Dwi Maulidina; Hadiah Fitriyah (Indonesian Journal of Cultural and Community Development, 2024)
This study explores strategies to increase income in the Creative Jaya sandal home industry in Gresikan Village, Krian District, facing challenges such as limited market information and ineffective product promotion. Utilizing qualitative methods and SWOT analysis, the research identifies the SO (Strengths and Opportunities) strategy as most promising for revenue enhancement. Findings suggest prioritizing product quality, fostering customer relationships, improving human resource capabilities, innovating products, and securing reliable suppliers. The study highlights the significance of government support and provides actionable insights for small-scale home industries, particularly in sandal craftsmanship, to achieve sustainable growth and competitiveness. Highlight: Challenges in Marketing: Limited information and strategic promotion affect revenue. SWOT Strategy: Strengths and opportunities enhance revenue in home industries. Key Actions: Prioritize quality, build customer relations, secure reliable suppliers. Keywoard: Home industry, Sandal craftsmanship, Revenue enhancement, Qualitative methods, SWOT analysis